2018
DOI: 10.1186/s13613-018-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of inter-hospital transportation in 431 transport survivor patients suffering from acute respiratory distress syndrome referred to specialist centers

Abstract: BackgroundThe acute respiratory distress syndrome (ARDS) is a life-threatening condition. In special situations, these critically ill patients must be transferred to specialized centers for escalating treatment. The aim of this study was to evaluate the quality of inter-hospital transport (IHT) of ARDS patients.MethodsWe evaluated medical and organizational aspects of structural and procedural quality relating to IHT of patients with ARDS in a prospective nationwide ARDS study. The qualification of emergency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
(32 reference statements)
2
15
3
1
Order By: Relevance
“…The majority of incidents were related to ECMO implantation or critical condition of the patient. This finding is in accordance with the observed rate of critical events in the DACAPO study, where 59 (13.6%) critical events occurred, with 42 being patient related [24]. The observed rates of ECMO implantation related complications are also in accordance with those by Brechot et al This indicates, that out-of-centre complications are most likely secondary to the procedure itself and not the absence of a vascular surgeon in our team.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of incidents were related to ECMO implantation or critical condition of the patient. This finding is in accordance with the observed rate of critical events in the DACAPO study, where 59 (13.6%) critical events occurred, with 42 being patient related [24]. The observed rates of ECMO implantation related complications are also in accordance with those by Brechot et al This indicates, that out-of-centre complications are most likely secondary to the procedure itself and not the absence of a vascular surgeon in our team.…”
Section: Discussionsupporting
confidence: 91%
“…Brechot et al published a mean SOFA score of 14 (IQR 10–16), also comparable to the observed scores in our cohort [22]. Mirroring this finding are data from the DACAPO study group, who reported a mean SOFA of 11 (IQR 8–13) [24].…”
Section: Discussionsupporting
confidence: 90%
“…All issues identified in this evaluation were discussed during team debrief and addressed in subsequent practice. Prevalence of critical events reported in our evaluation was relatively low compared with results previously reported by Blecha et al, 15 who reported 9 transportation delays, 5 equipment-related and 3 transportation vehicle-related issues during retrieval of 431 patients, 52 of whom were retrieved on ECMO.…”
Section: Discussioncontrasting
confidence: 72%
“…Of the total of 167 completed retrievals, 31 (17.9%) were declined ECMO following on-site review either due to perceived futility following on-site review 13 or improvement in patient's condition 14 as a result of advice given by the retrieving team 15 or improvement on conventional therapy since initial (Figure 1). The mean age of the patients was 42.1 (AE15.9) years, the mean BMI was 31.0 (AE9.1) and 98 (57%) were male.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence on interhospital transfer of ARDS patients, but these transfers have always been conducted for single patients. 6 , 7 Every interhospital or intrahospital transfer is known to be a risk period for the critically ill patient. 8 , 9 In the case of ARDS patients, interhospital transfers have been shown to be associated with minor deterioration of the patients’ condition; however, the risks are to be balanced with the expected benefits, such as the opportunity for the patient to access to specialized facilities such as extracorporeal membrane oxygenation (ECMO).…”
Section: Introductionmentioning
confidence: 99%